Effect of the fractional composition of the solid components of coal–water fuel on the characteristics of ignition and combustion - Lapin D. A. Dmitry Aleksandrovich; Lyrshchikov S. Yu. Sergey Yurievich; Strizhak P. A. Pavel Alexandrovich; Shevyrev S. A. Sergey Aleksandrovich (2017, 2017)
Title screen